Justice of the peace in Peru - Ardito Vega, Wilfredo (2002)
In recent years, the constitutions of Colombia, Peru, Bolivia, Ecuador and Venezuela have recognized the power to administer justice to the authorities of indigenous communities. In Peru, for historical reasons, this recognition is expressed in relation to the authorities of the peasant and native communities. However, in many cases, this power is not exercised by the traditional leaders of the population, but by the people that the Judicial Power has appointed: the justices of the peace.